2017
DOI: 10.1002/slct.201601590
|View full text |Cite
|
Sign up to set email alerts
|

Decoralin Analogs with Increased Resistance to Degradation and Lower Hemolytic Activity

Abstract: Decoralin is an antimicrobial peptide with activity against microorganisms and pronounced hemolytic activity. Decoralin analogs have been proposed, and the results indicated that when isoleucine at position 6 was substituted by phenylalanine residue, the peptides exhibited increased resistance towards enzymes action. Besides that, lower hemolytic activity was obtained for [Pro] 4 -Decoralin-NH 2 and [Phe] 6 -Des[Thr] 11 -Decoralin-NH 2 ; this effect is probably due to their poor helical tendency.[Arg] 1 -Decor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 22 publications
2
46
0
2
Order By: Relevance
“…Torres et al . observed it and designed new Dec‐NH 2 analogs, in order to evaluate the effect of changes in some specific biophysical properties . They found that increasing the positive net charge in one unit and maintaining the mean hydrophobicity of Dec‐NH 2 would improve its activity decreasing its toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Torres et al . observed it and designed new Dec‐NH 2 analogs, in order to evaluate the effect of changes in some specific biophysical properties . They found that increasing the positive net charge in one unit and maintaining the mean hydrophobicity of Dec‐NH 2 would improve its activity decreasing its toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…This peptide was obtained from Oreumenes decoratus wasp venom [9], and in the same study, it was also reported a decoralin amidated analog, decoralin-NH 2 (Dec-NH 2 ) that was slightly more active than the native molecule. Torres et al observed it and designed new Dec-NH 2 analogs, in order to evaluate the effect of changes in some specific biophysical properties [10]. They found that increasing the positive net charge in one unit and maintaining the mean hydrophobicity of Dec-NH 2 would improve its activity decreasing its toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Dec‐NH 2 and eight analogs were synthesized, which as we previously showed, have antimicrobial activity against bacteria and fungi ,. The analogs were designed to preserve specific physicochemical features, such as net positive charge, hydrophobicity, and amphipathicity, which are important for interactions with membranes, for bioactivity against microorganisms and cancer cells,, and for suppressing hemolytic activity .…”
Section: Characterization and Theoretical Physicochemical Properties mentioning
confidence: 91%
“…Torres et al . had previously identified the following two important features associated with the activity of this decoralin family of peptides against bacteria and fungi: their tendency to adopt a helical structure and the increase in their net positive charge.…”
Section: Characterization and Theoretical Physicochemical Properties mentioning
confidence: 99%
“…[1] In general, AMPs are small, cationic, characterized by their ability to fold in amphipathic conformations and present a wide diversity in amino acid composition and secondary structures. [3][4][5][6][7][8][9] Cancer is caused by the growth and spreading of abnormal cells in an uncontrolled manner and has become the major cause of death. They present a broad spectrum of antimicrobial activity against Grampositive and negative bacteria, fungi, enveloped viruses, parasites, and some types of cancer.…”
Section: Introductionmentioning
confidence: 99%